To Preserve a Benevolent Attitude - Slater, Verona Wylie (Tufts Archival Research Center, 2006)
Verona Slater describes her experience with religion as a child, the daughter of a minister, and how her beliefs in wisdom, kindess, courage and strneght have been shaped by these experiences.